Cardiac rehabilitation and mortality reduction after myocardial infarction: the emperor's new clothes?: Evidence against cardiac rehabilitation. Issue 13 (4th May 2013) - West, Robert; Jones, Dee
Abstract : No trial of cardiac rehabilitation (CR) following myocardial infarction (MI) (not even the WHO European collaborative) demonstrates significant reduction of mortality, as do trials of secondary prevention. There is potential conflict of interest when therapists report self-evaluations. Reviews of published reports exaggerate publication bias. Meta-analyses show no significant effect of CR on mortality in recent years – since 1990, 23 trials, 6527 patients, relative risk 1.01 (0.88–1.15). It does no service to MI patients – or rehabilitation therapists – to repeat claims derived from poolings of historic trials, undertaken before many significant advances in diagnosis, acute treatment and effective secondary prevention. While CR has a role in good medical/nursing practice and continuity of care, rehabilitation therapists could be more effective elsewhere in the NHS.